2010
DOI: 10.1179/026708410x12687356948634
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and complex magnetic permeability of thermally sprayed NiZn ferrite coatings for electromagnetic wave absorbers

Abstract: Ferrites are iron containing, non-conducting ceramics, which exhibit magnetic properties. One of the most common is (Ni,Zn) 1 Fe 2 O 4 . Bulk ferrites are typically made by conventional ceramic sintering. However, manufacture of thick coatings is of growing interest, and deposition by thermal spraying is potentially attractive. The present paper reports work on the development of (Ni 0?549 Zn 0?333 Co 0?028 Mn 0?049 )O 0?958 Fe 2 O 3 based powder feedstock by self-propagating high temperature synthesis and coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Therefore, they can be used as electronic components, magnetic memories and magnetic substrates for magnetic catalysts [26]. It is reported that the exchange interaction between hard and soft magnetic phases can improve the magnetic, dielectric and microwave absorption properties [27,28]. In other words, magnetic composite ferrites with high coercivity can be used as microwave absorbing materials especially that the compound has hard and soft magnetic phases.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they can be used as electronic components, magnetic memories and magnetic substrates for magnetic catalysts [26]. It is reported that the exchange interaction between hard and soft magnetic phases can improve the magnetic, dielectric and microwave absorption properties [27,28]. In other words, magnetic composite ferrites with high coercivity can be used as microwave absorbing materials especially that the compound has hard and soft magnetic phases.…”
Section: Resultsmentioning
confidence: 99%
“…1 On the other hand, materials with an ultrafine structure, especially nanostructure, have been recognised to exhibit attractive physical, chemical and mechanical properties. [2][3][4][5][6] Nanostructured coatings have been considerably investigated and reported to possess superior toughness, adhesion, spallation, wear, corrosion and thermal resistance compared to their conventional coarse grained counterparts. [7][8][9][10] Several fabrication routes are under development to produce nanostructured coatings.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Studies of iron based materials have attracted much interest in the last few years from both fundamental and applicative points of view. [8][9][10][11][12][13] Surface modification of magnetic nanoparticles (NPs) is a frequently used method to promote the performance of NPs as nanobiomaterials. In the recent decades, magnetic NPs, especially Fe 3 O 4 and c-Fe 2 O 3 , have attracted increasing interest because of their outstanding properties, including superparamagnetism and low toxicity and, as a result, their potential applications in various fields, especially in biotechnology and biomedicine, such as cell sorting, enzyme immobilisation, biosensing and bioelectrocatalysis, separation and purification.…”
Section: Introductionmentioning
confidence: 99%